Antioksidan Alternatif Untuk Menangkal Bahaya Radikal Bebas Pada Kulit - Ayu Nirmala Sari (Elkawnie, 2015)
Skin damage will impair human health. One of the causes of skin damage are free radicals form ultra violet rays. Antioxidants are needed to stabilize free radicals. Alternative sources of antioxidants which can be used to block the effects of free radicals on the skin are skin lotion of fruit black mangrove (Rhizophora mucronata Lamk.) and sunscreen of waste corn cob (Zea mays L). Mangrove fruit methanol extract shown to function as a source of natural antioxidants, which have very strong antioxidant activity, so the lotion containing fruit extracts exact mangrove can be used as inhibitors of free radicals on the skin. In addition, it has been proven that the active compound contained in a corn cob has the ability as a sunscreen active ingredient, with the highest SPF value.